Differently Expression Analysis and Function Prediction of Long Non-coding RNAs in Duck Embryo Fibroblast Cells Infected by Duck Tembusu Virus - Lin, Yun; Yang, Jing; He, Dalin; Li, Xudong; Li, Jing; Tang, Yi; Diao, Youxiang (Frontiers in Immunology, 2020)
Duck Tembusu virus (DTMUV), the causative agent of egg-drop syndrome, has caused substantial economic losses to duck industry. DTMUV infection leads to profound changes of host cells, including transcriptome and proteome. However, the lncRNA expression profile and the biological function of lncRNA have not been revealed. Therefore, DTMUV was used to inoculate duck embryo fibroblast cells (DEFs) for high-throughput RNA-sequencing (RNA-Seq). The results showed that 34 and 339 differently expressed lncRNAs were respectively identified at 12 and 24 h post-infection (hpi). To analyze their biological functions, target genes in cis were searched and the regulatory network was formed. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that the target genes were strongly associated with immune system, signaling molecular and interaction, endocrine system, and signal transduction. The differently expressed lncRNAs were selected and veriﬁed by quantitative real-time polymerase chain reaction (RT-qPCR). Our study, for the first time, analyzed a comprehensive lncRNA expression profile in DEFs following DTMUV infection. The analysis provided a view on the important roles of lncRNAs in gene regulation and DTMUV infection.